The Hausman-MaCurdy Controversy - Why do results differ between studies? - Matias Eklöf; Hans Sacklén (Uppsala University, Department of Economics, 1997)
The two perhaps most influential empirical labor supply studies carried out in the U.S. in recent years, Hausman (1981) and MaCurdy, Green & Paarsch (1990), report sharply contradicting labor supply estimates. In this paper we seek to uncover the driving forces behind the seemingly irreconcilable results. Our findings suggest that differences with respect to the estimated income and wage effects can be attributed to the use of differing nonlabor income and wage measures, respectively, in the two studies. Monte Carlo experiments suggest that the wage measure adopted by MaCurdy et al might cause a severely downward biased wage effect such that data falsely refute the basic notion of utility maximization.
urn:nbn:se:uu:diva-2399
Keywords: J22; 330; Labor supply; Slutsky condition; maximum likelihood estimation